Comparative efficacy of precut over a pancreatic duct stent and transpancreatic precut sphincterotomy for difficult biliary cannulation in ERCP - YAO Wenfei, QI Yang, LI Qianyi, WU Yuquan, XU Ruiyun, YAO Wei, KONG Lei, LI Nengping (Waike lilun yu shijian)
Objective To compare the efficacy of precut over a pancreatic duct stent (PPDS) and transpancreatic precut sphincterotomy (TPS) for difficult biliary cannulation in endoscopic retrograde cholangiopancreatography (ERCP). Methods A retrospective analysis was conducted on the clinical data of all consecutive patients underwent ERCP by the same doctor in our hospital between April 2019 and March 2023. According to the selected method during difficult biliary cannulation when guidewire entered pancreatic duct unintendedly, the patients were divided into two groups,1) PPDS group: placing a pancreatic duct stent first, then using a needle knife to cut bile duct sphincter on the surface of the pancreatic duct stent, preserving pancreatic duct sphincter, and then selectively cannulate bile duct; 2) TPS group: precut through pancreatic duct sphincter first, then a pancreatic duct stent was placed, and bile duct was selectively cannulated. The success rate of biliary cannulation and ERCP-related complication between the two groups were compared. Results Among 762 ERCP patients, 84 patients were enrolled in this study, 44 patients in PPDS group, and 40 patients in TPS group. In PPDS group, 42 patients (95.4%, 42/44) had successful biliary cannulation. No post-ERCP pancreatitis(PEP), bleeding, perforation occurred in PPDS group. In TPS group, 39 patients (97.5%, 39/40) had successful biliary cannulation. Four patients (10.0%, 4/40) had PEP in PPDS group, no bleeding or perforation occurred. All patients were cured. The success rate of biliary cannulation between two groups had no significant difference（P>0.05）, while the rate of PEP had significant difference(P<0.05). Conclusions Both PPDS and TPS are good choice for difficult biliary cannulation with high success rate of biliary cannulation. PPDS is more suitable for patients with high-risk factors for PEP, while TPS is a simple technique.